Distance Learning Design: A Problem-Based Learning with Flipped Classroom Model through improving student learning outcomes and learning motivation - Laswadi, Laswadi; Setiawan, M Eval; Efyanti, Yasni; Pentang, Jupeth Toriano; Taresh, Sahar M (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
The purpose of this study is to improve learning outcomes in the form of cognitive abilities and student learning motivation through the development of the learning design Problem-Based Learning within flipped classroom model. The study used quasi-experimental research with One Group Pretest-Post Test Design. In the research process, instruments are needed in the form of (1) multiple-choice tests as instructional cognitive measurements of students, and (2) observation sheets of learning motivation measurements in the form of motivational rubrics developed based on arcs rubrics. The increased motivation was analyzed based on the results of the questionnaire produced based on the ARCS rubric develop the results of student learning (post-test) are calculated using the t-test and then continued with the conclusion of the learning hypothesis. Based on the hypothesis test, it was found that 0.000 <0.005, it can be concluded that there is a real difference between learning outcomes in the pretest and posttest data. This result means that the application of this learning method can improve the learning outcomes of students. In addition, there is an increase in motivation in the learning process with flipped classrooms and problem-based learning design. Increased student motivation in the learning process I to learning III by 3% to 13%. But from this study, it is expected that there will be further research using the same model in other subjects and by using a larger sample and taking measurements on affective and psychomotor aspects